Wnt/β-catenin signaling regulates brain-derived neurotrophic factor release from spinal microglia to mediate HIV(1) gp120-induced neuropathic pain - Zhou, Xinxin (Mol Pain, 2020)
HIV-associated neuropathic pain (HNP) is a common complication for AIDS patients. The pathological mechanism governing HNP has not been elucidated, and HNP has no effective analgesic treatment. Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophic factor family related to the plasticity of the central nervous system. BDNF dysregulation is involved in many neurological diseases, including neuropathic pain. However, to the best of our knowledge, the role and mechanism of BDNF in HNP have not been elucidated. In this study, we explored this condition in an HNP mouse model induced by intrathecal injection of gp120. We found that Wnt3a and β-catenin expression levels increased in the spinal cord of HNP mice, consequently regulating the expression of BDNF and affecting hypersensitivity. In addition, the blockade of Wing-Int/β-catenin signaling, BDNF/TrkB or the BDNF/p75NTR pathway alleviated mechanical allodynia. BDNF immunoreactivity was colocalized with spinal microglial cells, which were activated in HNP mice. Inhibition of spinal microglial cell activation by minocycline relieved mechanical allodynia in HNP mice. This study helped to elucidate the role of the Wing-Int/β-catenin/BDNF signaling axis in HNP and may establish a foundation for further research investigating the Wing-Int/β-catenin/BDNF signaling axis as a target for HNP treatment.